Influence of Outside Directors on Performance of Japanese Companies - Matsuoka, Hiroyuki; Manabe, Kazuhiro (International Journal of Management and Sustainability, 2016)
The reinforcement of corporate governance in Japan is one of the pillars of Japan’s growth strategy which companies have to regain "the power to earn". In this respect, the influence of the introduction of outside director on performance of Japanese companies still remains controversial. This research reached one conclusion by introducing a new viewpoint. Especially, we examine how outside director is associated with earnings persistence in Japanese listed companies. Many prior researches agree that company profitability tend to move to the average over time. Earnings persistence is a concept of time series tendency of earnings. Prior research developed some empirical measurements of earnings persistence. If outside director has positive impact on the profitability, then earnings persistence of companies with higher proportion of outside director are higher than that of companies with lower proportion of outside director. Our data used for this study are from Nikkei Economic Electronic Databank System (NIKKEI NEEDS) by Nikkei Media Marketing, Inc. NIKKEI NEEDS has data for all listed companies on stock markets of Japan. We focus on all companies listed on the first or second section of the Tokyo Stock Exchange, and select 13,376 firm-years in the period from 2003 to 2014. We test the effect of outside directors on performance using the empirical model used by many accounting studies. Our results indicate that outside director has positive impact on the profitability in critical situations, while he or she has little positive and negative impact on the profitability normal situations. We conclude that impact of outside director on corporate performance is narrow in Japan.